FORMATION AND PROCESSING OF ENTROPY-MANIPULATED CORRECTING SIGNAL CODES IN WIRELESS SENSOR NETWORKS - Voronych, Artur; Nykolaychuk, Yaroslav; Hladyuk, Volodymyr (International Journal of Computing, 2014)
It is described a systematization of theoretical bases and analytical expressions for evaluation of entropy measures. It is showed a characteristic of signal corrective codes of Galois field. It is described the use of entropic manipulation and corrective signal codes in wireless sensor networks. It is founded that entropy approach of applying the corrective codes of Galois field is the most effective and promising for the formation and processing of signals during transmission in wireless sensor networks.